Особливості бюджетування як інструмент контролю витрат на ремонти основних засобів підприємства - Маркус, Ольга Віталіївна; Markus, Olha V. (Житомирський державний технологічний університет, 2014)
Досліджено особливості застосування бюджетування як методу контролю витрат, пов’язаних з ремонтом, реконструкцією та модернізаеією основних засобів підприємства. Рекомендовано впроваджувати його на рівні структурних підрозділів підприємства. Розкрито можливості застосування системи планово-попереджувалиних ремонтів, що сприятиме підвищенню ефективності ремонтних робіт, зниженнй їх собівартості. Запропоновано заходи з автоматизації планово-попереджувальних ремонтів на базі використання сучасних засобів обчислювальної техніки, що сприятиме підвищенню оперативності та ефективності контролю без збільшення трудомісткості робіт. Внесені пропозиції щодо удосконалення системи управлінсикого обліку з використанням методу бюджетування, для контролю витрат на ремонт основних засобів.

In the article the features of the application as a control method of budgeting the costs associated with the repair, reconstruction and modernization of fixed assets of the company. It is recommended to implement it at structural divisions. Reveals the possibility of the system planned preventive maintenance that will improve the efficiency of repairs, reducing their cost. The measures for automating routine preventive maintenance based on the use of modern computer technology that will improve the efficiency and effectiveness of control without increasing the complexity of work. The paper included proposals to improve the management accounting system using budgeting to control the cost of repairs of fixed assets. Effective prediction, control repair costs, which is compared to the actual performance of the budget, and analysis of deviations allows time to identify problem areas and offer reasonable steps to Eliminate weaknesses. It also enables enterprises to obtain competitive advantage and provide greater efficiency in the use of financial resources.
Aplication of budgeting as a tool to control spending on repairs of fixed assets of enterprise
Keywords: основні засоби; fixed assets; витрати; costs; бюджетування; budgeting